2020
DOI: 10.1111/bjep.12355
|View full text |Cite
|
Sign up to set email alerts
|

How executive functions contribute to reading comprehension

Abstract: Background. Executive functions have been proposed to account for individual variation in reading comprehension beyond the contributions of decoding skills and language skills. However, insight into the direct and indirect effects of multiple executive functions on fifthgrade reading comprehension, while accounting for decoding and language skills, is limited. Aim. The present study investigated the direct and indirect effects of fourth-grade executive functions (i.e., working memory, inhibition, and planning)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 82 publications
2
44
0
4
Order By: Relevance
“…Several EF skills contribute directly to reading: cognitive flexibility (also called shifting; Georgiou, & Das, 2018; Kieffer, Vukovic, & Berry, 2013), inhibitory control (Kieffer et al, 2013; Potocki, Sanchez, Ecalle, & Magnan, 2017), working memory (Nouwens, Groen, Kleemans, & Verhoeven, 2020; Potocki et al, 2017; Sesma, Mahone, Levine, Eason, & Cutting, 2009), planning (Nouwens et al, 2020; Sesma et al, 2009), and attentional control (Conners, 2009). These contributions make sense, given the complexity of reading processes that require the ability to direct attention to particular aspects of text (attentional control), build and maintain a model of text meaning while decoding the words in the text (working memory), suppress distracting information (inhibitory control), shift continuously between key processes (cognitive flexibility), and plan and manage one’s progression toward the goal of a reading task (planning).…”
Section: Active Self‐regulation Is Central To Readingmentioning
confidence: 99%
“…Several EF skills contribute directly to reading: cognitive flexibility (also called shifting; Georgiou, & Das, 2018; Kieffer, Vukovic, & Berry, 2013), inhibitory control (Kieffer et al, 2013; Potocki, Sanchez, Ecalle, & Magnan, 2017), working memory (Nouwens, Groen, Kleemans, & Verhoeven, 2020; Potocki et al, 2017; Sesma, Mahone, Levine, Eason, & Cutting, 2009), planning (Nouwens et al, 2020; Sesma et al, 2009), and attentional control (Conners, 2009). These contributions make sense, given the complexity of reading processes that require the ability to direct attention to particular aspects of text (attentional control), build and maintain a model of text meaning while decoding the words in the text (working memory), suppress distracting information (inhibitory control), shift continuously between key processes (cognitive flexibility), and plan and manage one’s progression toward the goal of a reading task (planning).…”
Section: Active Self‐regulation Is Central To Readingmentioning
confidence: 99%
“…Turning, more specifically, on the relationship between EFs and early literacy skills, findings showed that EF tasks have domain-general predictive power for pre-academic abilities that are less automatic and require more effortful processing of information, such as word writing at preschool age (Schwarz & Shaul, 2018); in addition, it emerged that inhibition tasks that involve a verbal component are more tightly related to early reading skills compared to nonverbal inhibition tasks (Foy & Mann, 2013). However, literacy skills might be less related to EFs when considering more automatized skills (e.g., letter knowledge, word recognition) (Blair et al, 2015), but EFs turn out to be meaningful predictors of higher order linguistic skills such as reading comprehension (Nouwens et al, 2020). Phonological WM is highly related to reading skills (Gathercole & Baddeley, 1993;Wagner & Torgesen, 1987), although it is an object of debate whether phonological WM has a causal role in literacy development or whether it involves, as reading skills do, access to representations that underlie phonological awareness tasks (Melby-Lervåg et al, 2012).…”
Section: Cognitive Predictors Of Early Literacy and Numeracy Skillsmentioning
confidence: 99%
“…Cerebral blood flow imbalance of the MCA was negatively associated with working memory performance in children after pediatric AIS. Working memory is a crucial functional domain that underlies many higher-order cognitive functions such as reading, arithmetics and self-regulation processes [59]. Mean working memory performance was 0.55 standard deviations below the mean in the present patient sample and presents the most pronounced deficit among the cognitive functions measured.…”
Section: Discussionmentioning
confidence: 51%